Orsós Ferenc orvosprofesszor, a Debreceni M. Kir. Tisza István Tudományegyetem 1923/24. tanévi rector magnificusa - Mudrák, József (Gerundium, 2015)
FERENC ORSÓS PROFESSOR OF MEDICINE, THE RECTOR MAGNIFICUS OF ISTVÁN TISZA HUNGARIAN ROYAL UNIVERSITY IN DEBRECEN DURING THE ACADEMIC YEAR OF 1923/24. Ferenc Orsós was born in Temesvár, graduated from medical school in Budapest, worked in the Institute of Pathology in Debrecen, and as a hospital commander during the WWI. He was appointed a professor of pathology, and the rector of the University of Debrecen in the academic year of 1923/24. He was the professor of forensic medicine at the Péter Pázmány University from 1936 until 1944 when he leed to the West. Later on, from 1946 until his retirement in 1955 he worked as the teacher of artistic anatomy at the Art Academy in Mainz. he name of Ferenc Orsós is well-known even today, irstly in connection to the excavation of the Katyń mass graves, secondly to his active participation in the senate discussion of the so-called 3rd anti-jewish laws. His scientiic achievements have been acknowledged not just in his time, but also today, since several of his discoveries seem to be futureproof.